Practical approaches to teaching Shakespeare - Reynolds, Peter 1946- (Oxford Univ. Press, 1991)
This exclusive collection of the Bard's works has been designed specifically for readers new to Shakespeare's rich literary legacy. Each of the plays is presented unabridged and in large print, copiously annotated and preceded by a character summary and commentary. Brief scene synopses clarify confusing plots, while incisive essays describe the historical context and Shakespeare's sources. The explanatory notes are written clearly and simply, illustrated, and positioned right next to the text -- no more flipping pages back and forth to squint over microscopic footnotes! Topics for further discussion, critical comments, related essays, and a chronology of Shakespeare's life and work are included among the appendices to each volume. The books boast fine black-and-white photographs of stagings of the plays at Shakespeare Festivals around the globe. From the wide margins and big print to the extent of explanatory notes -- the full text of each play is presented in the clearest and most accessible format available.
Keywords: Shakespeare, William <1564-1616>; Shakespeare, William <1564-1616> -- Study and teaching; Shakespeare, William -- 1564-1616; Englischunterricht; Literaturunterricht; Lehrmittel